Magnetorheological Fluid Based Devices Reported in 2013–2018: Mini-Review and Comment on Structural Configurations - Phu, Do Xuan; Choi, Seung-Bok (Frontiers in Materials, 2019)
This paper presents a mini-review of magnetorheological (MRF) fluid based devices (MRF devices in short) including of brake, clutch, damper, and mount reported from 2013 to 2018. MRF devices are normally designed based on three operating modes of MRF: flow mode, shear mode and squeeze mode. Each mode has its own characteristics for high performances of application systems. Therefore, numerous design configurations of MRF devices have been proposed by many researchers. In this article, among many different MRF devices, MRF brake, MRF clutch, MRF damper and MRF mount proposed for last 6 years are examined in the sense of structural configuration and operating principle. A certain advantages and demerits of each MRF device are also discussed. In addition, some useful design guidelines of MRF devices, which are absolutely different from the developed MRF devices so far, are provided to enhance design simplicity and control performance.